1998
DOI: 10.1183/09031936.98.12030742
|View full text |Cite
|
Sign up to set email alerts
|

A case of respiratory muscle weakness due to cytochrome c oxidase enzyme deficiency

Abstract: aaCytochrome c oxidase (COX) is a complex mitochondrial enzyme involved in oxidative phosphorylation. COX deficiency can result in a myopathy. We describe a patient with acute respiratory failure and pulmonary hypertension secondary to a partial COX enzyme deficiency. This is one of four reported cases with isolated late-onset COX deficiency involving muscle, sparing ocular or central nervous system function. This patient also illustrates the need to consider neuromuscular weakness in the differential diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Additionally, nine patients demonstrated diaphragmatic strength two standard deviations below the limit of normal for our laboratory. The finding of muscle weakness in a significant percentage of our patients was unexpected as previous reports of respiratory muscle weakness associated with this disorder have been limited to case reports of respiratory failure (34,35). Our data suggest that milder degrees of respiratory muscle weakness are common in patients with mitochondrial myopathies and may contribute, at least in part, to their symptoms.…”
Section: Discussionsupporting
confidence: 39%
“…Additionally, nine patients demonstrated diaphragmatic strength two standard deviations below the limit of normal for our laboratory. The finding of muscle weakness in a significant percentage of our patients was unexpected as previous reports of respiratory muscle weakness associated with this disorder have been limited to case reports of respiratory failure (34,35). Our data suggest that milder degrees of respiratory muscle weakness are common in patients with mitochondrial myopathies and may contribute, at least in part, to their symptoms.…”
Section: Discussionsupporting
confidence: 39%
“…Several case reports have suggested that patients with mitochondrial myopathy may manifest respiratory muscle weakness [47,48]. These reports describe 3 patients (ages 27-70) that presented with acute respiratory failure requiring prolonged weaning from ventilatory support.…”
Section: Respiratory Muscle Functionmentioning
confidence: 95%
“…In retrospect, they had experienced chronic respiratory symptoms which had been unrecognised, or had not come to medical attention [35][36][37][38]. In some instances, background respiratory dysfunction was worsened in the context of an acute illness or other metabolic stressors.…”
Section: Metabolic Myopathiesmentioning
confidence: 99%